2012
DOI: 10.1002/jcb.23372
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of RANKL‐dependent heme oxygenase‐1 is required for high mobility group box 1 release and osteoclastogenesis

Abstract: The differentiation of osteoclasts is regulated by several essential cytokines, such as receptor activator of nuclear factor κB ligand (RANKL) and macrophage colony-stimulating factor. Recently, high mobility group box 1 (HMGB1), a chromatin protein, also has been identified as one of these osteoclast differentiation cytokines. However, the molecular mechanisms that control HMGB1 release from osteoclast precursor cells are not known. Here, we report that RANKL-induced suppression of heme oxygenase-1 (HO-1), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 45 publications
3
70
0
Order By: Relevance
“…Similarly, we have also demonstrated that OCL differentiation or survival is regulated by NAC, or the oxidation agent hydrogen peroxide, and this is accompanied by changes in the shape and sizes of the cells. Furthermore, we recently demonstrated that the RANKL-mediated suppression of anti-oxidant enzyme heme-oxigenase 1 (HO-1) promoted high mobility group box 1 (HMGB1) release and OCL differentiation (7). Therefore, the use of anti-oxidants may enable the development of therapeutic agents for bone disorders such as osteoporosis and periodontitis.…”
Section: The Coffee Diterpene Kahweol Prevents Osteoclastogenesis Viamentioning
confidence: 99%
“…Similarly, we have also demonstrated that OCL differentiation or survival is regulated by NAC, or the oxidation agent hydrogen peroxide, and this is accompanied by changes in the shape and sizes of the cells. Furthermore, we recently demonstrated that the RANKL-mediated suppression of anti-oxidant enzyme heme-oxigenase 1 (HO-1) promoted high mobility group box 1 (HMGB1) release and OCL differentiation (7). Therefore, the use of anti-oxidants may enable the development of therapeutic agents for bone disorders such as osteoporosis and periodontitis.…”
Section: The Coffee Diterpene Kahweol Prevents Osteoclastogenesis Viamentioning
confidence: 99%
“…Bone marrow-derived macrophages (BMMs) were isolated as described previously (7). The BMMs were replated in culture plates and incubated in α-minimal essential medium (α-MEM) [Code: 135-15175, bicarbonate buffered with L-glutamine; Wako Pure Chemicals containing 10% FBS with 100 U/mL of penicillin and 100 μg/mL of streptomycin in the presence of M-CSF (50 ng/mL) and RANKL (50 ng/mL)] for 60 or 72 h until the cells differentiated into multinucleated mature OCLs.…”
Section: Cell Culturementioning
confidence: 99%
“…Although over-expression of HO-1 by transient gene vector suppresses the OCL differentiation, down-regulation of HO-1 by RNA interference enhances osteoclastogenesis (7). In addition, a recent study has shown that fisetin induces HO-1 in HUVECs (17).…”
Section: Effects Of Fisetin On the Expression Levels Of Oxidative Strmentioning
confidence: 99%
See 2 more Smart Citations